2008 IEEE Sensors 2008
DOI: 10.1109/icsens.2008.4716491
|View full text |Cite
|
Sign up to set email alerts
|

Thermal property determination of laminar-flowing fluids utilizing the frequency response of a calorimetric flow sensor

Abstract: We demonstrate that the thermal conductivity and diffusivity of fluids can be measured independently of their motion state utilizing a micromachined calorimetric sensor. The sensor membrane bears a heating resistor and two symmetrically arranged thermistors. By immersing the sensor into the laminarflowing sample fluid and applying an AC heating current, the frequency response of the thermistor temperatures can be exploited to evaluate the thermal properties of the fluid. We developed a novel analytical model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…As most of the state-of-the-art works [6][7][8] suggest, it is necessary to know the flow velocity in order to determine the thermal properties of the fluid. The natural solution is thus to stop the fluid motion or to bring the heat transfer process into a region where the fluid is basically motionless.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As most of the state-of-the-art works [6][7][8] suggest, it is necessary to know the flow velocity in order to determine the thermal properties of the fluid. The natural solution is thus to stop the fluid motion or to bring the heat transfer process into a region where the fluid is basically motionless.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers have also successfully used oscillatory (AC) thermal excitation to simultaneously determine k and α of stagnant or moving liquids [6,7]. The main drawback is that the flow speed must be known beforehand.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment it could be shown that only the heater and the downstream temperature sensor are necessary for determining gas concentration and flow speed. The fabrication process is presented in detail in a previous work [7]. …”
Section: IImentioning
confidence: 99%
“…Most research groups working on this problem use oscillating heat generation. In these investigations either the flow rate has to be known in advance or the sensors operate under no flow conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…AC driven calorimetric flow sensors are also used to characterize the physical properties of the fluid only when the flow conditions were already established [3,[8][9][10], i.e., the flow speed is known. Frequency analysis of thermal flow sensor does not represent any novelty itself [3,8,9,11,12].…”
Section: Introductionmentioning
confidence: 99%